Donor derived cell free DNA in lung transplant recipients rises in setting of allograft instability - Smith, Joshua B.; Peterson, Ryan A.; Pomponio, Raymond; Steele, Mark; Gray, Alice L. (Frontiers in Transplantation, 2024)
PurposeThe purpose of this study was to evaluate the correlation between longitudinal monitoring of donor-derived cell free DNA (dd-cfDNA) in lung transplant recipients and a “gold standard” of existing tools (pulmonary function testing, radiographic imaging, laboratory and bronchoscopy data, clinical judgment) to assess allograft function.Methods24 consecutive transplant recipients were prospectively enrolled in this study measuring dd-cfDNA levels monthly in the first year after bilateral lung transplant. Blinded clinical adjudications were performed at the same timepoints to categorize allograft function as stable (FEV1 within 10% of prior value or when compared to best two averaged post-transplant values) or unstable. When deemed unstable, etiology of unstable graft function was elicited based on available clinical data. We then evaluated the association between dd-cfDNA and the clinical impression of allograft function using linear mixed models which adjusted for patient-level covariates and time since transplant.ResultsUnstable allografts were associated with 54.4% higher measures of dd-cfDNA, controlling for time since transplant and demographic covariates [adjusted mean ratio (aMR) = 1.54, 95% CI: 1.25–1.91]. Females tended to have higher measures of dd-cfDNA (aMR = 1.90 95%CI: 1.14–3.16). A two-fold increase in dd-cfDNA was associated with declines in FEV1 and FVC of 0.047 and 0.066 L, respectively, controlling for time since transplant and demographic covariates (slope: −0.047 95%CI: −0.076 to −0.019, and slope: −0.066 95%CI: −0.097 to −0.035, respectively). Discussion: Donor derived cell free DNA presents a potential additional minimally invasive clinical tool in lung transplant allograft monitoring within the first year of transplant, with unstable allografts correlating with higher dd-cfDNA values.